Growth analysis of some maize cultivars on weedy condition. Issue 1 (February 2021) - Rahayu, M; Yudono, P; Indradewa, D; Hanudin, E
Abstract: This research purpose was to study the influence of weed on the growth process of some maize cultivars. It was held from March to July 2016 in Banguntapan, Bantul, Yogyakarata and Plant Production Laboratory, Agriculture Faculty, Gadjah Mada University. The experiment design was split plot based on randomized complete block design. The corn cultivars as the main plot consisted of Bisi 18, Bisi 2, Pertiwi 3, NK 22, NK 33, DK 959, DK 771, DK 95, P 23, Bima 19 uri, Bisma, and Sukmaraga while the presence of weed as a sub-plot consisted of non-weedy and weedy. Data were analyzed using variance analysis (ANOVA) and Duncan Multiple Range Test (DMRT) of 5 % significant. The results showed that there was an interaction between maize cultivar and weed presence to the leaf area index and specific leaf weight on 6 week after planting (WAP). Weed did not decrease net assimilation rate on 4-6 WAP and 6-8 MST. Weed also did not decrease specific leaf weight. Weed reduced leaf area index and biomass dry weight on 6 and 8 WAP and crop growth rate on 4-6 WAP and 6-8 WAP. DK 771 and Sukmaraga produced the highest dry weight.